2012
DOI: 10.1109/tmag.2012.2198199
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Minor Loop and Iron Loss Under Constant Voltage Type PWM Inverter Excitation

Abstract: The pulse width modulation (PWM) inverter is widely used for the control of motors. We showed that the iron loss under PWM inverter excitation is affected by the impedance of the excitation circuit. The dc voltage of PWM inverter, which is widely used, is constant and the control of motor is carried out by changing the modulation index. Therefore, the evaluation of iron loss under PWM excitation with constant dc voltage is necessary in order to investigate the behavior of iron loss in an actual motor. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The authors conclude that the material specific iron losses tend to increase when the modulation index decreases. One of the cause of this increase is that reducing the modulation index has for effect to widen the minor hysteresis loops in the material (5) . Under the assumption that the harmonic content of the PWM supplied voltage is only responsible for extra eddy current losses, some authors are able to propose analytical formulas of the iron losses caused by PWM in transformers (6) .…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude that the material specific iron losses tend to increase when the modulation index decreases. One of the cause of this increase is that reducing the modulation index has for effect to widen the minor hysteresis loops in the material (5) . Under the assumption that the harmonic content of the PWM supplied voltage is only responsible for extra eddy current losses, some authors are able to propose analytical formulas of the iron losses caused by PWM in transformers (6) .…”
Section: Introductionmentioning
confidence: 99%
“…0 v L dt · · · · · · · · · · · · · · · · · · · · · · · · · · · · (6) where N is the primary winding number, A c is the crosssectional area of the core, T s is the switching cycle, and v L is the inductor voltage. By adjusting v L , the iron loss under the desired B p condition can be measured.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…PWM inverter outputs have higher harmonic components superimposed in fundamental waveforms. Many studies have reported that, due to high harmonic components, iron loss of the motor core under PWM inverter excitation increases [7][8][9][10][11][12][13][14][15][16][17] by 10%-50% 10) compared with sinusoidal excitation. In these researches, magnetic hysteresis loops had many minor loops.…”
Section: Introductionmentioning
confidence: 99%